Early Primary Education Thai Textbooks and the Presentation of Parental Roles to Youths - Ingsatitanavan, Pornnapa; Numun, Wanna (JOURNAL OF SOUTHERN TECHNOLOGY, 2023)
In this article, the researcher asserts that the development of youths in early primary education is important. This can be proved upon consideration of Thai textbooks that are meant for nurturing youth behaviors and thoughts through the presentation of exemplary parental roles which can act as their role models in the future. The objective of this study was to examine parental roles presented in early primary education Thai textbooks that can be used as examples for young people. The scope of the study limits to the examination of parental roles in the early primary education PasaPatee Thai textbooks prepared by the Office of the Basic Education Commission (OBEC), the Ministry of Education. Documentary research method and descriptive analysis were employed in this study. Results revealed that the portrayal of parental roles in the textbooks can be classified in three areas: demonstrating good Thai citizenship, good occupation, and good family members. Furthermore, the study of the roles and responsibilities of parents as positive role models for youth from the early stages in Thai language primary education serves as a guideline to instill desirable qualities in young individuals. Their observation of parental roles in the textbooks can guide them to be good citizens which also meets the goal set by the government. This can be applied in real-life contexts that is suitable for Thai society.